Characterization of Malaysian Pectobacterium spp. from vegetables using biochemical, molecular and phylogenetic methods. - Golkhandan, Elham; Sijam, Kamaruzaman; Meon, Sariah; Mior Ahmad, Zainal Abidin; Nasehi, Abbas (Springer Netherlands, 2013)
In August 2011, vegetable crops showing symptoms of maceration and water soaked lesions on their tuber, leaf, and fruit were collected from four major vegetable growing states in Malaysia including Pahang, Johor, Melaka and Selangor. The majority of the causal organisms isolated from infected tissues (52 strains) were identified as Pectobacterium spp. based on PCR amplification of the pectate lyase (pel) gene and amplification of the 16S-23S rRNA (ITS) with G1 and L1 primers. Physiological and biochemical assays divided Malaysian Pectobacterium species into two main groups: Pectobacterium wasabiae and Pectobacterium carotovorum subsp carotovorum. Partial sequence of PCR product from reaction of putative Pectobacterium spp. with 16S rRNA confirmed the results obtained from physiological and biochemical assays used for identification of the bacterium. Application of specific primers such as Eca1F/Eca2r, Br1f/L1r, EXPCCF/EXPCCR, and also ITS-PCR following by RFLP by restriction enzyme (RsaI) successfully differentiated Malaysian P. wasabiae and P. carotovorum subsp carotovorum isolates from other species and subspecies of Pectobacterium. Phylogenetic analysis of Malaysian isolates with housekeeping genes (mdh, gapA) grouped Malaysian P. carotovorum subsp carotovorum and P. wasabiae in the same cluster with P. carotovorum subsp carotovorum (Ecc380) and P. wasabiae (SCRI488) respectively.